Permanence and Extinction of a Generalized Gause-Type Predator-Prey System with Periodic Coefficients - Jinhuo Luo (Abstract and Applied Analysis)
We study the permanence and extinction of a generalized Gause-type predator-prey system with periodic coefficients. We provide a sufficient and necessary condition to guarantee the predator and prey species to be permanent and a sufficient condition for the existence of a periodic solution. In addition we prove that when the predator population tends to extinction, the prey population keeps oscillating above a positive population level.